Hubungan Antara Online Customer Review dengan Minat Beli Konsumen - Mohamad Robby Nugraha Dwinanda; Aning Sofyan (UNISBA Press, 2023)
Abstract. Individuals tend to view online customer reviews as trustworthy because online customer reviews are created by consumers who are not seen as trying to manipulate. In addition, consumers provide feedback by providing an honest evaluation of the advantages and disadvantages of a product. The purpose of this study was to determine the relationship between uploads of consumer writings about Eiger objection letters and consumer buying interest. The method used in this study is quantitative with a correlational type. The population in this study were 3,125 Eiger Bandung consumers. The sampling technique used is probability sampling with accidental sampling technique, the number of samples is 96 people. Data collection techniques using questionnaires / questionnaires, and documentation. Data analysis technique using spearman rank. The results of the study show that (1) there is a relationship between online customer reviews and consumer buying interest in Eiger products; (2) there is a relationship between review quality and consumer buying interest in Eiger products; (3) there is a relationship between review quantity and consumer buying interest in Eiger products; (4) there is a relationship between review valance and consumer buying interest in Eiger products; (5) there is a relationship between credibility sources and consumer buying interest in Eiger products. Abstrak. Individu cenderung melihat ulasan pelanggan online dapat dipercaya karena ulasan pelanggan online dibuat oleh konsumen yang tidak dianggap mencoba memanipulasi. Selain itu, konsumen memberikan umpan balik dengan memberikan evaluasi yang jujur ​​tentang kelebihan dan kekurangan suatu produk. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara unggahan tulisan konsumen tentang surat keberatan Eiger dengan minat beli konsumen. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan tipe korelasional. Populasi dalam penelitian ini adalah konsumen Eiger Bandung sebanyak 3.125. Teknik pengambilan sampel yang digunakan adalah probability sampling dengan teknik accidental sampling, jumlah sampel 96 orang. Teknik pengumpulan data menggunakan angket/angket, dan dokumentasi. Teknik analisis data menggunakan rank spearman. Hasil penelitian menunjukan bahwa (1) terdapat hubungan antara online customer review dengan minat beli konsumen terhadap produk Eiger; (2) terdapat hubungan antara review quality dengan minat beli konsumen terhadap produk Eiger; (3) terdapat hubungan antara review quantity dengan minat beli konsumen terhadap produk Eiger; (4) terdapat hubungan antara review valance dengan minat beli konsumen terhadap produk Eiger; (5) terdapat hubungan antara credibility sources dengan minat beli konsumen terhadap produk Eiger.